2011
DOI: 10.1102/1470-7330.2011.0023
|View full text |Cite
|
Sign up to set email alerts
|

Extranodal manifestations of lymphoma on [18F]FDG-PET/CT: a pictorial essay

Abstract: Lymphoma is the seventh most common type of malignancy in both sexes. It is a neoplastic proliferation of lymphoid cells at various stages of differentiation and affects lymph nodes with infiltration into the bone marrow, spleen and thymus. However, extra nodal involvement is frequently seen in many cases. With the development of dedicated positron emission tomography (PET) scanners with fused computed tomographic (CT) systems in the same gantry, [18F]fluorodeoxyglucose (FDG)-PET/CT has become a major tool in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 27 publications
1
30
0
3
Order By: Relevance
“…3 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET)/CT of the whole body, though experimental in this indication, would give more information about the systemic spread of the disease. 4 FDG-PET/CT is superior to contrast-enhanced CT scan of the whole body in staging high-grade lymphomas as it is a functional image of the body. 5 Various studies have demonstrated an upstaging of lymphomas with PET/CT as compared with contrast CT scan in approximately 20% of cases, with a change in treatment decision occurring in fewer than 15% of cases.…”
Section: Hematologist's Expert Opinionmentioning
confidence: 99%
“…3 18 F-fluorodeoxyglucose positron emission tomography (FDG-PET)/CT of the whole body, though experimental in this indication, would give more information about the systemic spread of the disease. 4 FDG-PET/CT is superior to contrast-enhanced CT scan of the whole body in staging high-grade lymphomas as it is a functional image of the body. 5 Various studies have demonstrated an upstaging of lymphomas with PET/CT as compared with contrast CT scan in approximately 20% of cases, with a change in treatment decision occurring in fewer than 15% of cases.…”
Section: Hematologist's Expert Opinionmentioning
confidence: 99%
“…It is a locally aggressive form of lymphoma involving the nasal cavity, septum, paranasal sinuses and hard palate with the erosion of underlying bone unlike DLBC. 2 These lesions are also intensely FDG-avid. Our patients had DLBC and T cell variants showing intense FDG-avidity too.…”
Section: Discussionmentioning
confidence: 97%
“…1, 2 Although PEL can arise in almost every organ, gastrointestinal tract is the most frequently involved localization. Its incidence accounts for 30–40% of all extranodal cases in hospital and population-based series published so far.…”
Section: Introductionmentioning
confidence: 99%
“…Adrenal insufficiency is known to have associations with other conditions, therefore, knowledge of this can lead to prompt diagnosis and earlier management once this diagnosis is made. Lymphomas can cause adrenal insufficiency by involving adrenal glands, although the majority of them arise from lymph nodes, up to a quarter develop from extranodal sites [4]. Disseminated non-Hodgkin's lymphoma (NHL) can involve adrenal glands in up to 24% of patients as reported in an autopsy study [5].…”
Section: Introductionmentioning
confidence: 99%